Rút gọn biểu thức sau F=(x^2+x+1)(x^2-x+1)(x^2-1)

Question

Rút gọn biểu thức sau
F=(x^2+x+1)(x^2-x+1)(x^2-1)

in progress 0
Helga 4 years 2020-10-28T20:43:39+00:00 2 Answers 94 views 0

Answers ( )

    0
    2020-10-28T20:45:13+00:00

    `F=(x^2+x+1)(x^2-x+1)(x^2-1)`

    `=(x^2+x+1)(x^2-x+1)(x-1)(x+1)`

    `=[(x^2+x+1)(x-1)][(x^2-x+1)(x+1)]`

    `=(x^3-1)(x^3+1)`

    `=x^6-1`

    0
    2020-10-28T20:45:22+00:00

    Đáp án:

     

    Giải thích các bước giải:

     `F=(x^2+x+1)(x^2-x+1)(x^2-1)`

    `F=(x^2+x+1)(x^2-x+1)(x-1)(x+1)`

    `F=(x^3-1)(x^3+1)`

    `F=x^6+x^3-x^3-1`

    `F=x^6-1`

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )